2016
DOI: 10.1073/pnas.1523824113
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane/cell wall perturbation activates a novel cell cycle checkpoint during G1 in Saccharomyces cerevisiae

Abstract: Cellular wound healing or the repair of plasma membrane/cell wall damage (plasma membrane damage) occurs frequently in nature. Although various cellular perturbations, such as DNA damage, spindle misalignment, and impaired daughter cell formation, are monitored by cell cycle checkpoint mechanisms in budding yeast, whether plasma membrane damage is monitored by any of these checkpoints remains to be addressed. Here, we define the mechanism by which cells sense membrane damage and inhibit DNA replication. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(83 citation statements)
references
References 64 publications
7
76
0
Order By: Relevance
“…Conceptually, this trade-off suggests that the double mutant initially overshoots the optimum when nystatin concentrations are low, because the costs associated with each ergosterol mutation are combined (perhaps destabilizing the plasma membrane); by contrast, when nystatin concentrations are high, the optimum is shifted even farther away, and extreme reductions in ergosterol and potentially other sterols are needed for the yeast to survive, at which point the double mutant is most fit (see, e.g., Blanquart et al [42] for a theoretical exploration of this phenomenon). Because membrane damage can trigger cell cycle arrest in yeast [43], another possible explanation for the results observed at high concentrations of nystatin is that single mutants experience cell cycle arrest, reducing growth rate, whereas the additional stress caused by the combination of two mutations and high concentrations of nystatin may cause a checkpoint failure in double mutants, allowing the cells to bypass arrest and continue dividing (personal communication, C. Nislow to J. Ono).…”
Section: Discussionmentioning
confidence: 99%
“…Conceptually, this trade-off suggests that the double mutant initially overshoots the optimum when nystatin concentrations are low, because the costs associated with each ergosterol mutation are combined (perhaps destabilizing the plasma membrane); by contrast, when nystatin concentrations are high, the optimum is shifted even farther away, and extreme reductions in ergosterol and potentially other sterols are needed for the yeast to survive, at which point the double mutant is most fit (see, e.g., Blanquart et al [42] for a theoretical exploration of this phenomenon). Because membrane damage can trigger cell cycle arrest in yeast [43], another possible explanation for the results observed at high concentrations of nystatin is that single mutants experience cell cycle arrest, reducing growth rate, whereas the additional stress caused by the combination of two mutations and high concentrations of nystatin may cause a checkpoint failure in double mutants, allowing the cells to bypass arrest and continue dividing (personal communication, C. Nislow to J. Ono).…”
Section: Discussionmentioning
confidence: 99%
“…In Saccharomyces cerevisiae, the cell wall integrity (CWI) maintenance mechanism is intricately involved in this coordination (Levin, 2011). A dedicated checkpoint monitoring yeast CWI, regulates cell cycle progression depending on the state of the wall (Levin, 2011; Kono et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it was also shown that a dedicated cell cycle checkpoint exists at the G1/S transition, which in response to plasma membrane and/or CWD inhibits cell cycle progression until the damage has been repaired (Fig. A) (Kono et al ).…”
Section: Regulation Of Cell Cycle Progression By the Ecm In Yeast Andmentioning
confidence: 99%